(untitled) (Communications in Computational Physics, 2008)
The ability to reliably detect coronary artery disease based on the acoustic noises produced by a stenosis can provide a simple, non-invasive technique for diagnosis. Current research exploits the shear wave fields in body tissue to detect and analyze coronary stenoses. The methods and ideas outlined in earlier efforts [6] including a mathematical model utilizing an internal strain variable approximation to the quasi-linear viscoelastic constitutive equation proposed by Fung in [19] is extended here. As an initial investigation, a homogeneous two-dimensional viscoelastic geometry is considered. Being uniform in θ, this geometry behaves as a one dimensional model, and the results generated from it are compared to the one dimensional results from [6]. To allow for different assumptions on the elastic response, several variations of the model are considered. A statistical significance test is employed to determine if the more complex models are significant improvements. After calibrating the model with a comparison to previous findings, more complicated geometries are considered. Simulations involving a heterogeneous geometry with a uniform ring running through the original medium, a θ-dependent model which considers a rigid partial occlusion formed along the inner radius of the geometry, and a model which combines the ring and occlusion are presented.